Echoes of Scripture in the letters of Paul - Hays, Richard B. (Yale University Press, 1989)
"Paul's letters, the earliest writings in the New Testament, are filled with allusions, images and quotations from the Old Testament. This book investigates Paul's appropriation of Scripture from a perspective based on recent literary-critical studies of intertextuality."--Amazon.com
Keywords: Bible. -- Epistles of Paul -- Relation to the Old Testament.; Bible. -- Old Testament -- Relation to the Epistles of Paul.; Bible. -- Epistles of Paul -- Criticism, interpretation, etc.; Bible. -- Old Testament -- Quotations in the New Testament.; Bible -- New Testament. -- Épîtres de Paul -- Relation avec l'Ancien Testament.; Bible -- New Testament. -- Épîtres de Paul -- Critique, interprétation, etc.; Bible -- A.T. -- Citations dans le Nouveau Testament.; Bible. -- Ancien Testament -- Citations dans le Nouveau Testament.; Bible. -- Epistles of Paul; Bible. -- Old Testament; Bibel -- Altes Testament; Paulus, -- Apostel, Heiliger. -- Briefe.; Paulus (Apostel). -- Briefe.; RELIGION -- Biblical Studies -- New Testament.; Brieven van Paulus.; Oude Testament.; Criticism, interpretation, etc.; Quotations